Pelaporan Corporate social Responsibility (CSR) Perbankan Syariah dalam Perspektif Syariah Enterprise Theory (Studi Kasus pada Laporan Tahunan PT Bank Syariah Mandiri) - B1031141056, Siti Jenab (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
Â AbstractThis study aims to analyze the reporting of corporate social responsibility (CSR) in Islamic banking based on concept of sharia enterprise theory. The research was done by analyzing how the Bank Syariah Mandiri (BSM) reported their corporate social responsibility . This study uses a descriptive-qualitative method of annual reports BSM and then analysis based on the disclosure of social responsibility based on sharia enterprise theory. The result of this research is showed that BSM has done all five items in syaria enterprise theory whic is vertical accountability for Allah, horizontal accountability towards its customers, indirect stakeholdersÂ  and nature. However, there are some items in horizontal accountability towards indirect stakeholders and nature that haven't fully been done by BSM itself.Kata kunci: Corporate Social Responsibility, bank syariah, Syariah Enterprise Theory, Bank Syariah Mandiri.Â Referensi Achua, J. K. (2008). Corporate Social Responsibility In Nigerian Banking System. Society and Business Review. Vol 3Alamsyah, H. (2011). Membangun Kapasitas dan Memperkuat Kontribusi Perbankan Syariah dalam Percepatan Pembangunan Ekonomi. Keynote speech deputi gubernur Bank Indonesia pada acara seminar akhir tahun perbankan syariah, (Online), (http://www.bi.go.id, diakses 14 Desember).Al-Qurâ€™an dan Terjemahannya. (2005). Departemen Agama Republik Indonesia.Amalia, A. (2007). Analisis Pelaporan Tanggung Jawab Perusahaan. Skripsi tidak diterbitkan. Makassar: fakultas Ekonomi Universitas Hasanuddin.Chapra, M. U & Habib, A. (2008). Coorporate Governance Lembaga Keuangan Syariah. Jakarta : P.T Bumi Aksara.Dusuki, A. W & Dar, H. (2005). Stakeholdersâ€™ Preception Of Corporate Social Responsibilty Of Islamic Banks: The 6th Internasional Confrence On Islamic Ekonomic and Finance.Farook, S & Lanis, R. (2005). Banking on Islam? Determinants Of Corporate Social Responsibility Discloure. The 6th Internasional Cofrence on Islamic Ekonomic and Finance.Gantino, R. (2016). Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2008 â€“ 2014. Journal Dinamika Akuntansi dan Bisnis. Vol. 3(2) Hadi, N. (2011). Corporate Social Responsibility (CSR). Yogyakarta: Graha Ilmu.Hamsyi, N. F (2017). Analisis Penentuan Margin Pembiayaan Murabahah pada PT. Bank Syariah X Cabang Pontianak. Jurnal Ekonomi Bisnis dan Kewirausahaan (JEBIK), Volume: 06 No. 3, 175-186Hardiansyah. Lingkungan, Masyarakat dan Tanggung Jawab Sosial Perusahaan â€“ CSR, (online), ( http://fema.ipb.ac.id.)Ikatan Akuntan Indonesia. PSAK No. 01 (Revisi 2009). (online), (http://staff.blog.ui.ac.id., diakses pada 19 Juni 2009).Kartini, D. (2009). Corporate Social Responsibility: Transformasi Konsep Sustainability Management dan Implementasi di Indonesia. Jakarta: Refika Aditama.Khasanah, Z & Yulianto, A. (2015). Islamic Corporate Governance dan Pengungkapan Islamic Social Reporting Pada Bank Umum Syariah. Accounting Analysis Journal.Kurniawati, M. (2009). Pengaruh Mekanisme Corporate Governance, Kinerja Keuangan dan Kinerja Lingkungan Terhadap Pengungkapan Islamic Social Reporting (ISR) (Studi Empiris pada Perusahaan â€“ Perusahaan yang Termasuk Dalam Daftar Efek Syariah (DES) dan Mengikuti PROPER Tahun 2011 â€“ 2015)Laporan Tahunan (2010) PT Bank Syariah Mandiri, (Online), https://www.syariahmandiri.co.id/Mansur, S. (2012). Pelaporan Corporate Social Responsibility Perbankan Syariah dalam Perspektif Syariah Enterprise Theory. Makassar : Program Sarjana (S1) Universitas Hasanuddin.Meutia, I. (2010). Menata Pengungkapan CSR di Bank Islam (Suatu Pendekatan Kritis). Jakarta: Citra Pustaka Indonesia.Moh. N. (1988)., Metode Penelitian. Jakarta: Ghalia Indonesia.Muhammad. (2005). Pengantar Akuntansi Syariah. Jakarta: Salemba Empat.Mulyanita, S. (2009). Pengaruh Biaya Tangung Jawab Sosial Perusahaan terhadap Kinerja Perusahaan Perbankan. Skripsi tidak diterbitkan. Lampung: Fakultas Ekonomi Universitas Lampung.Mursitama, T, dkk. (2011). Corporate Social Responsibility di Indonesia (Teori dan Implementasi). Institute for Development of Economic and Finance (INDEF).Nawawi, K & Astriani, F. (2010). Peran penyaluran dana Corporate Social Responsibility (CSR) dalam meningkatkan kepercayaan nasabah. Bogor: Fakultas Agama Islam Universitas Ibnu Khaldun.Nugroho, F. F.A. (2011). Analisis Hubungan antara Pengungkapan Corporate Social Responsibility (CSR) dan Karakteristik Tata Kelola Perusahaan pada Perusahaan Manufaktur Di Indonesia. Skripsi tidak diterbitkan. Semarang: Fakultas Ekonomi Universitas Diponegoro.Sembiring, E. R. (2003). Faktor-Faktor yang Mempengaruhi Pengungkapan Tanggung Jawab Sosial Perusahaan. Jurnal Telaah Akuntansi, Volume: 01 No. 01 Juni 2003, hal. 01-21.Solihin, I. (2009). Corporate Social Responsibility (CSR). Jakarta: Salemba Empat.Sugandi, R. Kualitatif Deskriptif, (Online), (http://rubiantosugandi.blogspot.com)Sugiyono. (2005). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Trisnawati. R . (2012). Pengukuran Tanggung Jawab Sosial Perusahaan Perbankan Syariah di Indonesia. JAAI. Vol. 16.Triyuwono, I. (2007) Mengangkat â€sing liyan â€ untuk Formulasi Nilai Tambah Syariâ€™ah. Simposium Nasional Akuntansi X Unhas. 1-21.Umar, H. (2009). Metode Penelitian untuk Skripsi dan Tesis. Jakarta: Rajawali PersUndang-Undang Republik Indonesia Nomor 10 Tahun 1998 tentang Perubahan atas Undang-Undang Nomor 7 Tahun 1992 tentang Perbankan. 1998. Jakarta: Departemen Hukum dan HAM.Untung, H. B. (2008). Corporate Social responsibility. Jakarta: Sinar Grafika.Yulinarti. (2010).Â  Pengaruh Kinerja Keuangan Bank Syariah Indonesia Terhadap Pengungkapan Tanggung Jawab Sosial (CSR Discloure) Berdasarakan Shariah Enterprise Theory (Studi Empiris Bank Syariah di Indonesia).Yusuf, M. Y. (2010). Model Pelaksanaan Csr Bank Sariah: Kajian Empiris Pembiayaan Mikro Baitul Mal Aceh. Jurnal Ekonomi Islam vol. IV, No. 2.Zappi, G. (2007). Corporate responsibility in the Italian banking industry: creating value through listening to stakeholders. Corporate Governance, Vol. 7 Iss: 4, pp.471 â€“ 475Â